(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The nature of deformation and stress distribution in steel-concrete ribbed composite slab that is part of the space module of the steel and concrete grid-cable composite structure with span of 30 m were investigated. The plate was made with 20 mm thick and the size in terms 1.5×1.5 m. The plate has 30 mm height and 50 mm width ribs that giving the plate additional rigidity. Strengthening steel-concrete composite plate is provided with woven nets from steel wire by a diameter of 0.9 mm and a cell size of 12×12 mm. Connections woven reinforcing nets with each other is performed using embedded parts. The ribs were reinforced with rods of class A400C diameter of 6 mm. The design is made from the fine concrete C25/30. Analysis of stressstrain state the design was made with a numerical method. For the modeling of the physical and mechanical properties of the materials of the plates have been reduced characteristics. The main parameters were reduced modulus of elasticity plate and ribs.